Pengaruh Rasio Keuangan Terhadap Harga Saham - Primasatya, Rieswandha Dio; Arliana, Agatha (Politeknik Ganesha Medan, 2024)
This research aims to examine the impact of financial ratios such as Fixed Asset Turn Over, Return On Asset, Current Ratio, Total Asset Turnover, and Debt To Equity Ratio on stock prices of manufacturing companies in the consumer goods sector in Indonesia. The sample was selected from companies listed on the IDX for five consecutive years during the period 2015-2020, with consistent annual financial reports, and listed in the LQ45 during the 2020 period. The research findings indicate that Fixed Asset Turn Over has a significant negative relationship with stock prices, Return On Asset has a significant positive relationship with stock prices, Current Ratio shows a negative but not significant relationship with stock prices, Total Asset Turnover has a positive but not significant relationship with stock prices, and Debt To Equity Ratio has a negative and not significant relationship with stock prices. Subsequent research may consider other factors that influence stock prices and assess their impact on the variables under investigation